Updated competencies for the dental public health specialist: using the past and present to frame the future. (September 2016) - Weintraub, Jane A.; Gary Rozier, R.
Abstract: Objective: A new set of competencies for entry‐level specialists in dental public health (DPH) developed in 2016 updates the 1998 version. Our objective is to provide some context and perspective on this update. Methods: We discuss the evolution of this dental specialty, how it differs from other dental specialties, and its importance for the public's oral health. Some societal trends that provide the rationale for this update are summarized. The ways in which this set of competencies differs from the last version are described. Results: The first set of behavioral objectives was established in 1974 and updated at workshops in 1988 and 1997. Advanced population‐based knowledge and public health perspectives beyond that obtained in predoctoral dental education continue to be essential for the nation's oral health. Since 1998, the impact of the digital age, advances in science and technology, changes in population demographics, health status and increasing inequalities, treatment needs, prevention and treatment modalities, healthcare delivery systems, financing, personnel, legislation, and regulations have all influenced DPH practice. The updated competencies include guiding principles for the specialty, a new focus on social determinants of health, and more flexibility to address the increasing complexity and interdisciplinary nature of public health problems and the expanding knowledge and skills needed to address them. The rapid expansion of public health education might serve as an important pipeline for future DPH specialists. Conclusion: The updated competencies can guide the educational preparation of DPH specialists and are aligned with the rapidly changing environment.